Desain Pengembangan Media Pembelajaran Mahāratu al-Kalām Berbasis Articulane Story Line - Moh Zulkifli Paputungan (Universitas Muhammadiyah Gorontalo, 2022)
This study aims to find out the design of learning media based on Articulane Story Line in using Arabic language learning grade 11 MA which can be used by students. The method used is the D&D method, which is systematic to the process of design, development and evaluation with the aim to establish the empirical basis and creation of instructional products and tools and non-instructional tools as well as new enhanced models. The results show that there are several designs need to be added and reduced thus students can use the media properly and able to improving learning motivation